Analysis of incidence of motor neuron disease in England 1998–2019: use of three linked datasets - Burchardt, JM; Mei, XW; Ranger, T; McDermott, CJ; Radunovic, A; Coupland, C; Hippisley-Cox, J (Taylor and Francis, 2022)
Objective This study uses three linked datasets to provide an estimate of incidence of motor neuron disease (MND) in England from 1998 to 2019. Comparison is made to previous British studies. It examines age at diagnosis and ethnicity of those affected.